Efficacy of the β(2)-adrenergic receptor is determined by conformational equilibrium in the transmembrane region - Kofuku, Yutaka (Nature Pub. Group, 2012)
Many drugs that target G-protein-coupled receptors (GPCRs) induce or inhibit their signal transduction with different strengths, which affect their therapeutic properties. However, the mechanism underlying the differences in the signalling levels is still not clear, although several structures of GPCRs complexed with ligands determined by X-ray crystallography are available. Here we utilized NMR to monitor the signals from the methionine residue at position 82 in neutral antagonist- and partial agonist-bound states of β(2)-adrenergic receptor (β(2)AR), which are correlated with the conformational changes of the transmembrane regions upon activation. We show that this residue exists in a conformational equilibrium between the inverse agonist-bound states and the full agonist-bound state, and the population of the latter reflects the signal transduction level in each ligand-bound state. These findings provide insights into the multi-level signalling of β(2)AR and other GPCRs, including the basal activity, and the mechanism of signal transduction mediated by GPCRs.